What is a healthy community? Refugee youth's perspective on freedom, safety, and trust: a photovoice project. Issue 1 (2nd January 2023) - Springer, Paul; Franzen-Castle, Lisa; Gratopp, Emily; Schmader, Brenna
ABSTRACT: Immigration and forced migration have been on the rise globally because of a variety of political, social and economic factors. The association between forced migration and poor mental health is well documented, with many families and youth experiencing violence, loss of identity or status, racism, and discrimination. Despite these adversities, families and youth have leveraged individual and collective resources that have assisted in their integration, and overall well-being as they have acculturated to the United States (US). To explore the phenomenon of what refugee youth viewed as a healthy community during their transition to the US, a community based participatory research photovoice study was conducted with youth between 13-18 years of age. Through the photovoice process three main themes were identified by refugee youth that they felt were critical in making a healthy, thriving community, with thematic analysis revealing additional subthemes. Participants described how these themes were not only intertwined, but necessary for their social, emotional, and mental stability and the stability of members of their community. Implications regarding how to apply these results in both the clinical and human service fields are discussed.